Efforts To Increase Production Of Purple Eggplant (Solanum melongena L.) by Provisioning Terra Soil and NPK Fertilizer - Fajar Khoirunnisa; Sugiarto Sugiarto; Indiyah Muwarni (AGRONISMA, 2021)
Eggplant is a plant belonging to the Solanaceae family which is widely cultivated. Eggplant fruit is very popular with all circles. In Indonesia, the demand for eggplant continues to increase, so eggplant production needs to be increased. To increase eggplant production requires good quality land, but the development of land use as industrial needs causes land productivity to decrease, so it is necessary to improve land quality by adding soil improvement materials. This study aims to increase the yield of purple eggplant (Solanum melongen L) by providing soil improver and NPK fertilizer. This research was conducted in October 2020 – January 2021 in Agricultural Land, Karangjati Hamlet, Ardimulyo Village, Kec. Singosari, Malang Regency, the research method used a factorial randomized block design, namely: Factor 1 is T0 = No soil improver Novelgro terra, T1 = soil improver 1 ml/liter, Factor 2: P0 = No pearl NPK fertilizer, P1 = 75 kg/ ha, P2= 150 kg/ha, P3= 225 kg/ha, P4= 300 kg/ha. Data analysis used 5% analysis of variance test with 5% BNJ follow-up test, and regression analysis. Provision of soil enhancer is able to increase yields and reduce the use of inorganic fertilizers from the variable number of fruit per plant, total fruit weight per plant, fruit diameter and fruit length with optimum values (T0) 205.83 kg/ha, 204.28 kg/ha, 175 ,00 kg/ha and 161.07 kg/ha